'New kid on the block!!' Limited liability partnerships: the imminent business entity in Malaysia - Abd Ghadas, Zuhairah Ariff (LexisNexis Malaysia Sdn Bhd, 2009)
A business entity is basically a business structure which is recognised by law as a valid medium of carrying on trade. The most common business entities are sole proprietorships, partnerships (firms) and companies. In Malaysia, these are the only three types of business structures available in the market place. However, the business entities in other countries have expanded and developed to cater to business needs. One of the most recent types of business entities is the limited liability partnership ('LLP'). The LLP is a fascinating business structure as it could have the status of either a legal entity which is not a body corporate or one which is a body corporate. In the United Kingdom ('UK') for example, the off-shore LLPs, such as the Isle of Jersey LLP have the status of a legal entity which is not a body corporate whilst in the mainland; the UK LLPs have the status of a body corporate. In the South East Asian region, at present, LLPs are only available in Singapore. In Malaysia, there is a positive indication towards introducing LLPs in the near future as the Companies Comiision of Malaysia ('CCM')had published the consultation document on LLP Bill in April 2008. This paper intends to dicuss the features of the LLP as a new business entity and as the latest creation of a body corporate. Special reference is made to the Isle of Jersey LLPs and the UK LLPs to highlight the different types of LLP structures available, to the Singapore LLP Act 2005 and also to the CCM consultation document (April 2008) to underline the attributes of the LLPs which are proposed for Malaysia.